Penerapan Model Project-Based Learning pada Mata Pelajaran Instalasi Penerangan Listrik - Fikri Ramadhanil Haq; Elfizon Elfizon (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study was conducted to determine the effect of the application of the Project Based Learning learning model on the subject of Electrical Lighting Installation at SMK Negeri 1 Tanjung Raya. This study uses experimental research methods. The research design used is a pre-experimental one group pretest posttest design. This design involves one group being given a pretest (O1), given treatment (X) and given a posttest (O2). The population of this study were all class XI TITL at SMKN 1 Tanjung Raya with a research sample of class XI TITL 1. The first measurement was carried out before the sample was given treatment and the second measurement was after the sample was treated. The results obtained from the assessment of the performance of the psychomotor aspect using the rubric instrument for assessing student practice performance. Initial data was obtained from the pretest scores of the practical performance assessment of students, totaling twenty students, in this pretest assessment only six students passed the KKM. Furthermore, these students were treated with the application of the Project Based Learning learning model for two meetings. After that, students were given a posttest of practical performance assessment and obtained one hundred percent pass results. With the acquisition of these data, it can be concluded that with the application of the Project Based Learning learning model, the practical performance of XI TITL 1 students is greatly improved.